Effectiveness of Problem-Based Learning in Improving Elementary Students' Mathematics Achievement - Mei Kalimatusyaro; Vivi Afbriani; Zuni Humairoh; Fitrotin Hasanah (Universitas Sulawesi Barat, 2026)
The low mathematics achievement of elementary school students remains a common problem in learning. Although the Problem-Based Learning (PBL) model has been widely studied at the secondary education level, studies on its effectiveness in mathematics learning at the Madrasah Ibtidaiyah level are still relatively limited. Therefore, this study was conducted to analyze the implementation and effectiveness of the Problem-Based Learning (PBL) model in improving the mathematics achievement of fourth-grade students at Madrasah Ibtidaiyah Hidayatul Ulum Tempel Krian Sidoarjo. The study used a quantitative approach with an experimental design involving 48 students, consisting of 24 students in the experimental class and 24 students in the control class. Data were collected through observation, tests, and documentation, then analyzed using Analysis of Covariance (ANCOVA). The results showed that the implementation of the PBL model had a significant effect on students' mathematics learning achievement, with a significance value of <0.001. The average posttest score of the experimental class was 82.08, higher than the control class's 65.83. The normalized gain value of 0.62 indicates a moderate improvement in learning outcomes. Furthermore, the ANCOVA results yielded a Partial Eta Squared value of 0.279, indicating that the PBL model had a 27.9% effect on the variation in students' mathematics learning achievement, falling within the moderate to large effect category. These findings confirm that PBL is effective in improving mathematics learning outcomes while simultaneously fostering students' critical thinking and problem-solving skills. The implication of this study is that the PBL model can be used as an effective alternative learning strategy for Madrasah Ibtidaiyah teachers to improve the quality of student-centered mathematics learning.